Міжнародне співробітництво у протидії поширенню фейків як складова російсько-української війни - Логвиненко, Євгенія Сергіївна; Коршикова, Владислава Олегівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
International cooperation in countering the spread of fakes and disinformation related to the russian-Ukrainian war is important for ensuring information security and maintaining stability in our state. Fake news and disinformation may significantly undermine public trust, contribute to the escalation of conflict, and influence the domestic and foreign policies of countries. There has been identified the main directions of international cooperation in this area in the thesis of the report.